Hard-to-Survey Populations 2014
DOI: 10.1017/cbo9781139381635.016
|View full text |Cite
|
Sign up to set email alerts
|

Surveying cultural and linguistic minorities

Abstract: Cultural and linguistic minorities can be hard to survey either as the target population of interest or as a subpopulation of a general population survey. The challenges associated with studying these minorities are important to understand in order to assess and address the survey error that can be introduced when designing and implementing studies that include these groups. This chapter begins with a description of what constitutes cultural and linguistic minorities, based on a systematic review of the litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…For the convenience of the Belgian and Dutch managers, an independent native English speaker translated the questions into Dutch. The Dutch version was then back translated into English and checked against the original [ 30 ]. Our study was reviewed and approved by the Claremont Graduate University Institutional Review Board (application nr #1753).…”
Section: Methodsmentioning
confidence: 99%
“…For the convenience of the Belgian and Dutch managers, an independent native English speaker translated the questions into Dutch. The Dutch version was then back translated into English and checked against the original [ 30 ]. Our study was reviewed and approved by the Claremont Graduate University Institutional Review Board (application nr #1753).…”
Section: Methodsmentioning
confidence: 99%
“…Cross-cultural translation and adaptation of measures into another language have been undertaken in a number of studies [ 31 33 ]; however, no prior studies have been found that cross-culturally translated and adapted a colon cancer survey into the Urdu language. In one study [ 34 ], a CRC screening questionnaire was translated into Hindi and Gujarati using a bilingual-bicultural committee translation approach derived from translation methods proposed by Harkness and Mohler [ 35 ]. Likewise, in another study [ 36 ], a CRC screening survey assessed behaviours among English speaking SA’s in New York/New Jersey, but no information was provided on whether it was culturally adapted for this SA population.…”
Section: Discussionmentioning
confidence: 99%
“…The coding scheme of SQP is well defined, covers up to 60 characteristics depending on the survey question, of which only few are in fact subjective and thus up to the coder’s decision [ 38 ]. The developers of SQP have therefore decided not to present intercoder reliability but rather followed a team approach of review and adjudication, as suggested in other research fields such as survey translation [ 39 ]. While complete information about SQP 2.1 can be found elsewhere [ 36 ], for readers’ convenience we present in Annex I the SQP authorized coding of the 54 characteristics of the “economy” question as measured in the ESS.…”
Section: Datamentioning
confidence: 99%